Tingkat Ketahanan Klon Potensial Ubi Jalar Lokal Asal NTT Terhadap Hama Lanas (Cylas formicarius Fab.) - Yosep Seran Mau; Antonius SS Ndiwa; I GB Adwita Arsa (Universitas Lampung, 2011)
A laboratory experiment was carried out to evaluate the potential sweetpotato clones from NTT for the following objectives: 1) to determine resistance level of the clones to sweetpotato weevil (SPW), 2) to investitage the effect of genotype by tuber production site interaction on SPW-resistance level, 3) to identify SPW-resistant clones. Sweetpotato roots employed in the experiment were obtained from two production sites in the fields. The experiment was laid out in a Completely Randomized Design with a factorial treatment of two factors: sweetpotato genotype (10 clones) and root production sites (two sites). Experimental unit was replicated three times. Variables observed included percentage of SPW-injured root, severity of root injury, number of larva, pupae and imago, and root morphological characters. Quantitative data were subjected to analysis of variance while qualititave data were descriptively analyzed. Results of the study revealed significant interaction effect of genotype by tuber production site on severity of root injury and number of larva+pupae+imago. NBN-01 and NPL-02 produced the lowest (4.50%) and the greatest (67.03%) severity of root injury. NBN-01 was classified “resistant” and NPL-02 was “susceptible” while the remaining eight clones/check varieties were “moderately resistant” to SPW.